RETRACTED: Development of a management methodology to improve the competencies of employees with an assessment of their effectiveness - Kiryakova Marina; Ivanichkin Roman; Dolzhikov Dmitry; Yuvchenко Alexandra (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001